Current Versus Lifetime Depression, APOE Variation, and Their Interaction on Cognitive Performance in Younger and Older Adults. Issue 5 (June 2015) - Luciano, Michelle; Pujals, Ana Maria Fernández; Marioni, Riccardo E.; Campbell, Archie; Hayward, Caroline; MacIntyre, Donald J.; Porteous, David J.; McIntosh, Andrew M.; Deary, Ian J.
ABSTRACT Objective An interaction effect of depressive symptoms and APOE e4 allele status on cognitive decline has been shown in old age: e4 allele carriers with more depressive symptoms have faster cognitive decline than those with either depression or the e4 allele. We test this interaction effect on four cognitive domains, using a clinical depression measure comparing current versus lifetime depression. Methods 14, 379 individuals aged 18 to 59 years, and 3944 individuals aged 60 to 94 years from the Generation Scotland: Scottish Family Health Study participated. Linear-mixed models—accounting for participant relatedness and demographic and health indices—tested for effects of depression and APOE on cognitive abilities. Results There was no interaction between depression and APOE on cognition (p > .05). Current depression was associated with poorer speed (in both groups) and memory (18- to 59-year-olds); differences ranged from 0.01 to 0.03 standard deviation [SD]. For lifetime depression, cognitive performance was lower for digit symbol in younger adults, but higher for vocabulary in both younger (0.03 SD) and older (0.05 SD) adults. A negative effect of the APOE e4 allele on speed and memory was found in the group 60 years and older (effect sizes of 0.04 SD). Conclusions The absence of a depression by APOE interaction on cognitive abilities suggests that these synergistic effects only operate at the level of cognitive decline. This implies that it is those biological pathways especially affected by aging that become compromised further by the combined presence of depression and APOE e4 in an individual.